Q: How do you do this problem 2x plus 3y equals 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x-11

-2x plus 3y equals 1

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

2x-3y=13

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

Related questions

2x-11

-2x plus 3y equals 1

(2,7)

2x plus 3y

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

2x-3y=13

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

How do you add 2x plus 3y equals 18 in 5x-y equals 11

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11

4.34684352143

(3,3)